ACADEMIC MOBILITY: FACTORS OF DEVELOPMENT AND TRANSFORMATION - A. Yu. Kuznetsov; E. V. Vershinina (Высшее образование в России)
The article introduces the up-to-date research in academic mobility and the prospects for its development. Much attention is given to the factors of influence and contemporary trends in international education. Based on the above data there are made predictions for transformation of world academic mobility for the coming decade. The article is relevant due to the approval in 2017 of a state priority project on developing Russian education export capability.